Phytochemical Studies of Momordica Charantia Fruit: Seed Extraction via Aqueous Enzymatic Extraction and Pulp Maceration - Mohd Nesfu, Nadirah Zawani; Osman , Hasnah; Brosse, Nicholas; Muniglia, Lionel; Kamarulzaman, Ezatul Ezleen; Spina, Rosella; Laurain-Mattar, Dominique
The edible fruits of Momordica charantia or bitter melons have been used for over a decade in folk medicine for treatment of diabetes and malaria. The seeds usually have been discarded without any further use, however, it’s can be a good source of biomass. Hence, this research aimed to isolate active constituents from Momordica charantia seeds after aqueous enzymatic extraction and pulp after maceration.